Ecotopian Exceptionalism - Proctor, James D.; Berry, Evan (Journal for the Study of Religion, Nature and Culture, 2011)
Literature on the U.S. Paci?c Northwest generally paints the region in exceptionalist stripes, certainly in the deep connection its people maintain with an abundant natural landscape. Is Ecotopia exceptional? We interrogate the empirical basis for this claim, applying results from a mixed-method study of intentional and other communities in Oregon, and a comparative survey situating the Paci?c Northwest amidst other regions of the United States. Our focus was on imagined landscapes, both utopian and dystopian, as expressions of late-modern nature spirituality; we situated this emphasis in larger conversations around contemporary spiritual seeking and dwelling. Though there is no doubt that the biographies of those living in intentional communities and in the Paci?c Northwest are to some extent unique, our results suggest the need to temper this exceptionalist trope, both as a distinctive category of regional and spiritual identity, and as a salutary model of late-modern living worthy of the inordinate amount of attention it has received.